Corporate Governance (CG) and Environmental Reporting (ER): Evidence from China’s Financial and Non-Financial Sectors - Guo, Yiping (Transformations In Business & Economics, 2025)
This article empirically investigates the relationship between corporate governance (CG) and environmental reporting (ER) in financial and non-financial sectors of China for the period of 2015-2021. A self-generated environmental reporting index (ERI) is used with the help of manual content analysis. Moreover, the reporting frequency comparison (RFC) and paired sample t-test are applied to compare the environmental reporting in both sectors and report the potential change after and before the revision of Corporate Governance Guidelines in 2018 by the China Securities Regulatory Commission (CSRC). The results from multiple regression analyses suggest that foreign national directors significantly influence environmental reporting in the non-financial firms, while in the financial firms, the elements of corporate governance are found to exert no impact on environmental reporting. Parallel to this, the paired sample t-test and RFC show that environmental reporting is significantly greater in the non-financial firms than in the financial ones. This article offers novel contributions to the extant studies on CG and ER by employing a self-generated ERI to assess the ER in both financial and non-financial firms of China using the stakeholder theory as a theoretical lens. The policymakers and regulatory authorities in China and abroad should focus on the suggested governance framework to fulfil stakeholders’ needs and improve corporate environmental reporting.